The INFLUENCE OF ECONOMIC FREEDOM, MACROECONOMIC VARIABLES, AND THE COVID-19 PANDEMIC ON ECONOMIC GROWTH - Julian; Aida, Neli; Ratih, Arivina; Suparta, I Wayan (International Journal of Economics, Business, and Entrepreneurship, 2024)
The aim of APEC cooperation is to promote sustainable and inclusive economic growth, as well as enhance cooperation and economic integration among its members. This study aims to analyze the influence of economic freedom, foreign direct investment, international trade, labor force, inflation, and the Covid-19 pandemic on economic growth in the 19 APEC member countries using multiple linear regression method. This research examines the impact of economic freedom, foreign direct investment, international trade, labor force, inflation, and the Covid-19 pandemic on economic growth. The analysis results indicate that economic freedom, although important, may have limited impact in weak institutional settings. Conversely, foreign direct investment and international trade have proven to have significant positive effects by bringing capital, technology, and innovation as well as enhancing economic efficiency. Moreover, skilled labor force and controlled inflation also support economic growth. However, the Covid-19 pandemic has caused serious disruptions by disrupting supply chains, decreasing demand, and creating economic uncertainty, highlighting the importance of economic resilience and public health. These findings emphasize the importance of policies supporting these factors to drive sustainable economic growth.